Pengaruh Kecerdasan Intelektual, Kecerdasan Spiritual dan Kecerdasan Emosional terhadap Persepsi Etis Mahasiswa Akuntansi - Wijaya, Chandra; Mediatrix Ratna Sari, Maria (E-Jurnal Akuntansi; Vol 28 No 2 (2019), 2019)
This study aims to examine the effect of intellectual intelligence, spiritual intelligence and emotional intelligence on the ethical perceptions of accounting students. The object of research is active students of the 7th semester accounting study program at the Faculty of Economics and Business, Udayana University. The sample in this study amounted to 80 people. Data collection using the questionnaire method. The analytical method used in this study is multiple linear regression analysis. Based on the results of the research analysis, it can be said that Intellectual Intelligence has a positive influence on the Ethical Perceptions of Accounting Students, Spiritual Intelligence has a positive influence on Ethical Perceptions of Accounting Students, and Emotional Intelligence has a positive influence on Ethical Perceptions of Accounting Students. Keywords : Intellectual intelligence, spiritual intelligence, emotional intelligence, students, ethical perception.